Tenaliram ki rocak kahaniyan - Jauhari, Manju (Nai Dilli : Skai Buks Interneśanal, 2010)
Stories, based on the knowledge, intelligency and other activities of Tenaliram, the favourite court jester of King Krishnadevaraya; for juvenile
Na hindskom.
Keywords: hindska književnost -- proza; književnost za mlade -- lektira za srednju školu; priče o Tenalirami